2016
DOI: 10.1007/s13193-016-0578-1
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of Axillary Reverse Mapping and Clinicopathological Features Predicting ARM Node Metastasis in Breast Cancer—a Pilot Study

Abstract: The axillary reverse mapping (ARM) technique has been described as an attempt to map and preserve the upper extremity lymphatic drainage during axillary lymph node dissection (ALND) and/or SLNB. This technique is based on the hypothesis that the lymphatic pathway from the upper extremity is not involved by metastasis from primary breast cancer. The ARM node/s however, has been found, in various studies, to be involved with metastatic foci in patients with extensive axillary lymph node metastases. Therefore, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 18 publications
(25 reference statements)
3
7
0
Order By: Relevance
“…Twenty-nine articles published between January 2007 and January 2020 describing studies of 4954 patients were included in this meta-analysis [ 1 , 2 , [6] , [7] , [8] , [9] , 11 , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] ]. These included four randomized controlled trials [ 1 , [20] , [21] , [22] ] and 25 prospective non-randomized studies [ 2 , [6] , [7] , [8] , [9] , 11 , [14] , [15] , [16] , [17] , [18] , [19] , [23] , [24] , [25] ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Twenty-nine articles published between January 2007 and January 2020 describing studies of 4954 patients were included in this meta-analysis [ 1 , 2 , [6] , [7] , [8] , [9] , 11 , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] ]. These included four randomized controlled trials [ 1 , [20] , [21] , [22] ] and 25 prospective non-randomized studies [ 2 , [6] , [7] , [8] , [9] , 11 , [14] , [15] , [16] , [17] , [18] , [19] , [23] , [24] , [25] ].…”
Section: Resultsmentioning
confidence: 99%
“…(2016) [ 34 ] Prospective France ALND alone (172) Radioisotope ALND: 100%(172/172) NA 31%(54/172) SLNB + ALND: 27% 34 months Moderate quality 12/2009–12/2012 Kumar et al. (2017) [ 35 ] Prospective India ALND alone (20) Blue dye ALND: 75%(15/20) NA 13%(2/15) NA NA Moderate quality 05/2014–07/2015 Tummel et al. (2017) [ 6 ] Prospective USA SLND alone (472), ALND with or without SLNB (213) Blue dye + radioisotope SLND: 29%(138/472) ALND: 72%(153/213) 4%(18/472) 8%(7/74) SLNB: 3%(12/350) ALND: 21%(33/154) 26 months Moderate quality 06/2007–12/2013 Faisal et al.…”
Section: Resultsmentioning
confidence: 99%
“…In the study by Shivakumar et al, the most common location was lateral to the subscapular pedicle. 9 Though the location of the node was not so significant clinically, this parameter helps us to look for the nodes in the same location in subsequent cases. In the study by Nos et al, the nodes were seen above and below the intercostal nerves and in relation to the subscapular pedicle.…”
Section: Discussionmentioning
confidence: 99%
“…In a study by Shivakumar et al, intraoperative FNAC was used to detect metastatic ARM nodes. 9 It was concluded that nodes that are reported benign by intraoperative FNAC could be preserved safely to reduce lymphedema.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation